2016
DOI: 10.4317/jced.52381
|View full text |Cite
|
Sign up to set email alerts
|

CD166 expression in dentigerous cyst, keratocystic odontogenic tumor and ameloblastoma

Abstract: BackgroundCD166 is a glycoprotein of an immunoglobulin super family of adhesion molecules that has been associated with aggressive characteristics and high recurrence rate of tumors. Different odontogenic lesions exhibit considerable histological variation and different clinical behavior. In an attempt to clarify the mechanisms underlying this different behavior, the present study investigates the immunohistochemical expression of CD166 in these lesions.Material and MethodsIn this study 69 formalin-fixed, para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In the current study, the mean value of area percent of E-cadherin immunostaining was higher in OKC than SAB with no statistically significant difference between them. These results are in line with other's results (42) confirmed that adhesion molecules as (CD166) were expressed in ameloblastoma and OKC with no statistically significant difference between them. This could be explained by decreased to the negative reaction of E-cadherin in peripheral basal cells of both lesions where they express EMT phenotype and have the potential of focal invasion.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the mean value of area percent of E-cadherin immunostaining was higher in OKC than SAB with no statistically significant difference between them. These results are in line with other's results (42) confirmed that adhesion molecules as (CD166) were expressed in ameloblastoma and OKC with no statistically significant difference between them. This could be explained by decreased to the negative reaction of E-cadherin in peripheral basal cells of both lesions where they express EMT phenotype and have the potential of focal invasion.…”
Section: Discussionsupporting
confidence: 92%
“…16,20 This reflects the low activity in the proliferative component of the lining and consequently the known indolent course of DC. 3,5,16,21,22 An original finding in our research is the dual staining pattern, nuclear and cytoplasmic, with a predominance of the former pattern in the Am group of neoplastic nature. The cytoplasmic immunoreaction in the current study is justified by the study which proved the presence of BMI-1 in the inner mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 66%
“…2,3 A dentigerous cyst (DC) is the most common type of developmental odontogenic cyst with an indolent behavior and low recurrence rate. 4,5 These cysts are usually asymptomatic and are detected by routine radiographic examination except in large cases. 6 Larger cysts make great resorption of bone leading to thinning of cortex and eggshell cracking on palpation.…”
Section: Introductionmentioning
confidence: 99%
“…AMBL was found to express ABCG2 [ 13 ], ALDH1 [ 34 ], BMI1 [ 13 , 40 ], CD133 [ 13 ], CD166 [ 41 ], CD44 [ 12 , 31 , 44 ], and c-Myc [ 45 ] in peripheral and/or central cells of the parenchyma at variable extent and intensity levels, as well as CD34 in spindle-shaped stomal cells [ 10 ] and LGR5 [ 39 ] and NANOG [ 10 , 14 ] in both epithelial and stromal tumor components. AMBL cases were completely negative for OCT4 in four studies [ 10 , 12 , 28 , 32 ], and 100% positive in epithelial cells in two studies [ 14 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, five studies revealed SOX2 positivity in the majority of peripheral and/or central cells of epithelial islands [ 6 , 14 , 33 , 38 ] and/or stomal cells [ 6 , 10 ]. In most studies reporting stem cell marker expression data in different histopathological variants of AMBL, no significant differences were observed between the microscopic variants [ 6 , 13 , 34 , 41 , 42 , 45 ]. Unicystic AMBL expressed CD166 in the cystic lining [ 41 ], CD34 and NANOG in stromal cells [ 10 ], and SOX2 in epithelial [ 38 ] and stromal cells [ 10 ], while it was OCT4 negative [ 10 ].…”
Section: Resultsmentioning
confidence: 99%